Production of Thermostable Organic Solvent Tolerant Keratinolytic Protease from Thermoactinomyces sp. RM4: IAA Production and Plant Growth Promotion - Verma, Amit; Singh, Hukum; Anwar, Mohammad S.; Kumar, Shailendra; Ansari, Mohammad W.; Agrawal, Sanjeev (Frontiers in Microbiology, 2016)
There are several reports about the optimization of protease production, but only few have optimized the production of organic solvent tolerant keratinolytic proteases that show remarkable exploitation in the development of the non-polluting processes in biotechnological industries. The present study was carried with aim to optimize the production of a thermostable organic solvent tolerant keratinolytic protease Thermoactinomyces sp. RM4 utilizing chicken feathers. Thermoactinomyces sp. RM4 isolated from the soil sample collected from a rice mill wasteyard site near Kashipur, Uttrakhand was identified on the basis of 16S rDNA analysis. The production of organic solvent tolerant keratinolytic protease enzyme by Thermoactinomyces sp. RM4 was optimized by varying physical culture conditions such as pH (10.0), temperature (60°C), inoculum percentage (2%), feather concentration (2%) and agitation rate (2g) for feather degradation. The result showed that Thermoactinomyces sp. RM4 potentially produces extra-cellular thermostable organic solvent tolerant keratinolytic protease in the culture medium. Further, the feather hydrolysate from keratinase production media showed plant growth promoting activity by producing indole-3-acetic acid (IAA) itself. The present findings suggest that keratinolytic protease from Thermoactinomyces sp. RM4 offers enormous industrial applications due to its organic solvent tolerant property in peptide synthesis, practical role in feather degradation and potential function in plant growth promoting activity, which might be a superior candidate to keep ecosystem healthy and functional.